2007
DOI: 10.1002/psc.886
|View full text |Cite
|
Sign up to set email alerts
|

Substance P analogs containing α,α‐dialkylated amino acids with potent anticancer activity

Abstract: Six analogs (peptides 1-6) of the potent substance P (SP) derivative known as 'Antagonist D' were synthesized by substituting constrained amino acids Aib or Acp (cycloleucine, 1-amino cyclopentane carboxylic acid) at different positions in the Antagonist D sequence: D-Arg(1)-Pro(2)-Lys(3)-Pro(4)-D-Phe(5)-Gln(6)-D-Trp(7)-Phe(8)-D-Trp(9)-Leu(10)-Leu(11)-NH(2). In the preliminary in vitro antiproliferative screening of the analogs on different human cancer cell lines by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenylte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These results suggest that the in vivo activity of NK-1 and NK-2 antagonists may be a result of a cytostatic effect rather than a cytotoxic effect [173, 182]. Moreover, it has been reported that SP antagonists exert an antitumor action in a xenograft model of a human primary colon tumor cell line [183]. These findings are consistent with previous evidences showing that the inhibition of TAC1 expression by small interfering RNA in breast cancer cells shows a lack of tumorigenic phenotype and an inhibition of bone marrow metastasis in nude mice [39], while overexpression of NK-1 receptor leads to a transforming phenotype [184].…”
Section: Effects Of Nk-1 Receptors Antagonistsmentioning
confidence: 99%
“…These results suggest that the in vivo activity of NK-1 and NK-2 antagonists may be a result of a cytostatic effect rather than a cytotoxic effect [173, 182]. Moreover, it has been reported that SP antagonists exert an antitumor action in a xenograft model of a human primary colon tumor cell line [183]. These findings are consistent with previous evidences showing that the inhibition of TAC1 expression by small interfering RNA in breast cancer cells shows a lack of tumorigenic phenotype and an inhibition of bone marrow metastasis in nude mice [39], while overexpression of NK-1 receptor leads to a transforming phenotype [184].…”
Section: Effects Of Nk-1 Receptors Antagonistsmentioning
confidence: 99%
“…49 SP analogs have been found to cause tumor regression in a xenograft model of human primary colon tumor cell line. 50 For the treatment of locally advanced colorectal cancer, it is discussed that treatment with TNF␣ in combination with other treatments may be beneficial. 51 With the exception of BDNF, we found significant differences or tendencies for differences between the groups showing that the levels of the analyzed substances in plasma for UC patients were higher than those for the colonic carcinoma patients.…”
Section: Involvement Of Neuropeptides Neurotrophins and Tnf␣ In Colmentioning
confidence: 99%
“…Decreased affinity is associated with loss of hydrogen bond interactions due to a conformational change . Analogues that include α-helix or β-turn constraints in substance P, such as Aib or Acp (1-amino cyclopentane carboxylic acid), have shown potent anticancer activity . Structures of nonmammalian tachykinins such as eledoisin 109 , kassinin 110 , uperolein 111 , or phyllomedusin 112 show helical turns in SDS or DPC micelles …”
Section: Mammalian Gpcr-binding Peptide Hormonesmentioning
confidence: 99%
“…578 Analogues that include R-helix or β-turn constraints in substance P, such as Aib or Acp (1-amino cyclopentane carboxylic acid), have shown potent anticancer activity. 579 Structures of nonmammalian tachykinins such as eledoisin 109, kassinin 110, uperolein 111, or phyllomedusin 112 show helical turns in SDS or DPC micelles. [580][581][582][583] Turns have been stabilized in various cyclic analogues of substance P, such as 113, that are highly selective for NK-1 over NK-2 receptors.…”
Section: Somatostatinmentioning
confidence: 99%